Metabolic changes in kidney stone disease - Zhenzhen Xu; Xiangyang Yao; Chen Duan; Haoran Liu; Hua Xu; Hua Xu; Hua Xu (Frontiers in Immunology, 2023)
Kidney stone disease (KSD) is one of the earliest medical diseases known, but the mechanism of its formation and metabolic changes remain unclear. The formation of kidney stones is a extensive and complicated process, which is regulated by metabolic changes in various substances. In this manuscript, we summarized the progress of research on metabolic changes in kidney stone disease and discuss the valuable role of some new potential targets. We reviewed the influence of metabolism of some common substances on stone formation, such as the regulation of oxalate, the release of reactive oxygen species (ROS), macrophage polarization, the levels of hormones, and the alternation of other substances. New insights into changes in substance metabolism changes in kidney stone disease, as well as emerging research techniques, will provide new directions in the treatment of stones. Reviewing the great progress that has been made in this field will help to improve the understanding by urologists, nephrologists, and health care providers of the metabolic changes in kidney stone disease, and contribute to explore new metabolic targets for clinical therapy.